1996
DOI: 10.1074/jbc.271.1.349
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Signal Transduction and Growth Inhibition of Small Cell Lung Carcinomas Induced by Expression of GTPase-deficient Gα16

Abstract: Small cell lung carcinoma (SCLC) accounts for 20 -25% of primary lung cancers and is rapidly growing, widely metastatic, and rarely curable. Autocrine stimulation of multiple G protein-coupled neuropeptide receptor systems contributes to the transformed growth of SCLC. The ability of neuropeptide receptors to stimulate phospholipase C and mobilize intracellular Ca 2؉ indicates that G q family members of heterotrimeric G proteins are a convergence point mediating autocrine signaling by multiple neuropeptides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 30 publications
6
38
0
Order By: Relevance
“…According to this hypothesis, substance P derivatives preferentially bind to and stabilize neuropeptide receptors in a conformational state that activates G 12 and G 13 proteins, but not G q proteins (Jarpe et al, 1998). Thus, the substance P derivative o er a therapeutic approach to induce unbalanced, or discordant, signaling that is similar to what was previously accomplished in SCLC cells by retrovirus-mediated expression of constitutively active Ga q proteins or mutant PLCb proteins (Beekman et al, 1998;Heasley et al, 1996a).…”
Section: Signal Pathways Mediating Neuropeptide-stimulated Cellular Tmentioning
confidence: 79%
See 2 more Smart Citations
“…According to this hypothesis, substance P derivatives preferentially bind to and stabilize neuropeptide receptors in a conformational state that activates G 12 and G 13 proteins, but not G q proteins (Jarpe et al, 1998). Thus, the substance P derivative o er a therapeutic approach to induce unbalanced, or discordant, signaling that is similar to what was previously accomplished in SCLC cells by retrovirus-mediated expression of constitutively active Ga q proteins or mutant PLCb proteins (Beekman et al, 1998;Heasley et al, 1996a).…”
Section: Signal Pathways Mediating Neuropeptide-stimulated Cellular Tmentioning
confidence: 79%
“…This paradoxical inhibition of Ca 2+ mobilization by constitutively activated Ga q proteins appears to arise by way of a compensatory down-regulation of IP 3 -liganded Ca 2+ channels in the endoplasmic reticulum (Lobaugh et al, 1996;Quick et al, 1996). The resulting discordant signaling relative to the balanced signaling initiated by neuropeptide receptors is hypothesized to result in the marked reduction in SCLC cell growth that was observed (Heasley et al, 1996a). In another study, expression of a catalytically-inactive form of PLCb in SCLC cells which retains the sequences that interact with Ga q signi®cantly inhibited basal PKC activity and receptor-stimulated phosphatidylinositol hydrolysis, Ca 2+ mobilization and ERK activation, but not JNK activation (Beekman et al, 1998).…”
Section: Signal Pathways Mediating Neuropeptide-stimulated Cellular Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuropeptide-controlled growth of SCLC cells appears to be controlled by a delicately orchestrated interplay between various signaling pathways initiated by Gprotein-coupled neuropeptide receptors. Overexpression of GTPase-de®cient G-protein a subunits of the G q/11 family, for instance, results in discordant signal transduction and growth inhibition (Heasley et al, 1996). Likewise, expression of a constitutively active Raf kinase in SCLC cells leads to persistent ERK activation but inhibition of clonogenicity and growth arrest, most probably due to a marked induction of the cyclin-dependent kinase inhibitor p27 kip1 (Ravi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging theme is that the pathways signaling apoptosis overlap with those that mediate growth and di erentiation (LassignalJohnson et al, 1996;Fanidi et al, 1992;Gardner et al, 1993;Evan et al, 1992). In the context of signal transduction pathways, integration of signals initiated by growth factor and cytokine receptors, therefore, can commit a cell to either proliferation or apoptosis (Xia et al, 1995;Heasley et al, 1996;Gardner and Johnson, 1996). For example, we recently demonstrated that FGF-2 protects L929 cells from TNFa-stimulated apoptosis .…”
Section: Introductionmentioning
confidence: 99%